LEGAL ANALYSIS OF THE POSITION OF THE SERVICE BOND AGREEMENT BETWEEN THE COMPANY AND EMPLOYEES (CASE STUDY OF BREACH OF PERFORMANCE LAWSUIT OF PT FL TECHNICS INDONESIA AGAINST INDRA KURNIAWAN IN THE DECISION OF THE TANGGERANG DISTRICT COURT NUMBER 1000/PD - KURNIAWAN, C. FATWA ADDY; ANDREW BETLEHN, ANDREW BETLEHN; A SARAGI, PALTIADA (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
The tort case between PT FL Technics Indonesia and Indra Kurniawan centered on the violation of the service bond agreement that had been agreed by both parties. Based on this agreement, the company provided an opportunity for employees to attend training courses, with the obligation for employees to undergo service bonds according to a predetermined duration. However, the employee violated his obligation by resigning before completing the service bond period, resulting in an obligation for the employee to reimburse the training costs incurred by the company. This research uses a normative approach, which aims to analyze legal aspects based on relevant regulations and documents. The data sources used consist of primary, secondary, and tertiary legal materials, as well as primary data as support. The qualitative juridical analysis method is used to assess the collected data. In this case, the service bond agreement is not considered a work agreement, so disputes arising related to this agreement fall under the jurisdiction of the District Court, not the industrial relations court. Based on the Tangerang District Court Decision Number 1000/PDT.G/2023/PN TNG, Indra Kurniawan was proven to have committed a default, which requires him to be responsible for the breach of obligations arising from the agreement